Transforming growth factor beta signaling: The master sculptor of fingers. Issue 1 (6th May 2021) - Lorda‐Diez, Carlos I.; Duarte‐Olivenza, Cristina; Hurle, Juan M.; Montero, Juan A.
Abstract: Transforming growth factor beta (TGFβ) constitutes a large and evolutionarily conserved superfamily of secreted factors that play essential roles in embryonic development, cancer, tissue regeneration, and human degenerative pathology. Studies of this signaling cascade in the regulation of cellular and tissue changes in the three‐dimensional context of a developing embryo have notably advanced in the understanding of the action mechanism of these growth factors. In this review, we address the role of TGFβ signaling in the developing limb, focusing on its essential function in the morphogenesis of the autopod. As we discuss in this work, modern mouse genetic experiments together with more classical embryological approaches in chick embryos, provided very valuable information concerning the role of TGFβ and Activin family members in the morphogenesis of the digits of tetrapods, including the formation of phalanxes, digital tendons, and interphalangeal joints. We emphasize the importance of the Activin and TGFβ proteins as digit inducing factors and their critical interaction with the BMP signaling to sculpt the hand and foot morphology. Key Findings: TGFβ signaling promotes digit formation TGFβ signaling participates in digit tendons specification and maturation TGFβ signaling modulates digit joints specification and maturation